2015
DOI: 10.1080/01496395.2015.1040123
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of arsenic(V) oxyanion from aqueous solutions by using protonated chitosan flakes

Abstract: Arsenate (As(V)) oxyanion removal was achieved utilizing diverse chitosancontaining adsorbents, such as chitosan beads, protonated chitosan flakes, chitosan powder and chitosan functionalized with meso-2,3-dimercapto succinic acid (DMSA), and glutaraldehyde (GLA). Protonated Chitosan Flakes (PCF) showed to be the more effective adsorbent for the removal of As(V) oxyanion from aqueous solutions, removing 97% at the initial concentration of 0.500 mg/L. As(V) adsorption was favored by Langmuir model, with a maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…A protonated chitosan gel exhibited enhanced As (V) adsorption compared to chitosan powder (maximum ~88% versus ~40% at pH 3). Padilla-Rodriguez et al [ 54 ] also found that protonated chitosan flakes were more effective than chitosan powder for the removal of As (V) from aqueous solutions. Both the Ch–Rs and Ch–Pu blends in 1:2 and 1:5 ratios showed the highest As(V) removal efficiency (>90%) at a wide pH range (3 to 7) as compared to the unmodified red scoria (~90% only at pH 3) and pumice (<20%), as well as the blends at 1:10 ratio of chitosan–red scoria (>90% at pH 3 up to ~65% at pH 7) and chitosan–pumice (~85% at pH 3 up to ~19% at pH 7).…”
Section: Resultsmentioning
confidence: 99%
“…A protonated chitosan gel exhibited enhanced As (V) adsorption compared to chitosan powder (maximum ~88% versus ~40% at pH 3). Padilla-Rodriguez et al [ 54 ] also found that protonated chitosan flakes were more effective than chitosan powder for the removal of As (V) from aqueous solutions. Both the Ch–Rs and Ch–Pu blends in 1:2 and 1:5 ratios showed the highest As(V) removal efficiency (>90%) at a wide pH range (3 to 7) as compared to the unmodified red scoria (~90% only at pH 3) and pumice (<20%), as well as the blends at 1:10 ratio of chitosan–red scoria (>90% at pH 3 up to ~65% at pH 7) and chitosan–pumice (~85% at pH 3 up to ~19% at pH 7).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we observed that the chitosan-DES beads exhibited great efficacy in the elimination of the anionic dye Acid Blue 80 even after five successive uses when the adsorbent was subjected to acid treatment and then water-washed, maintaining the same adsorption capacity during the study, with no need to desorb the dye [9]. Protonated chitosan-based adsorbents have been scarcely tested for contaminants, as reported in few publications, most of them on metals and other inorganic contaminants [16][17][18][19][20][21] and very few ones on dyes [12,22,23]. Chitosan applications have been partly limited due to its dissolution in an acid medium.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the amino groups of chitosan can be protonated under acidic conditions (pH < 6.3) to form −NH 3 + , leading to the adsorption of anionic species such as fluoride, metal oxoanions, , and anionic dyes . Additionally, mechanical strength, thermal resistance, gas barrier property, antimicrobial property, and anion adsorption ability of the chitosan-based materials have successfully been improved upon the hybridization with clays including smectite clay minerals and layered double hydroxide. Despite the merits of the transformation of chitin to chitosan for the fabrication of functional biopolymer-based materials, the deacetylation process often requires strong alkaline conditions and, moreover, suffers from the weight loss which causes loss of strength in the final product . Therefore, the development of a methodology to use chitin without deacetylation, in addition to the alternative method of the deacetylation of chitin, is worth investigating.…”
Section: Introductionmentioning
confidence: 99%